2020
DOI: 10.1007/s00264-020-04731-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined serum biomarker analysis shows no benefit in the diagnosis of periprosthetic joint infection

Abstract: Purpose In many cases, the diagnosis of a periprosthetic joint infection (PJI) consisting of the clinical appearance, laboratory tests, and other diagnostic tools remains a difficult task. Single serum biomarkers are easy to collect, are suitable for periodical assessment, and are a crucial tool in PJI diagnosis, but limited sensitivity or specificity is reported in literature. The aim of this study was to combine the best-performing single serum biomarkers into a multi-biomarker model aiming to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…Systemic inflammation is associated with many orthopaedic diseases, such as periprosthetic joint infection [20,21], and surgical site infection [22,23]. PLR is a simple inflammatory marker that does not need any additional laboratory testing, and easily calculated by the platelet count/lymphocyte count formula.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic inflammation is associated with many orthopaedic diseases, such as periprosthetic joint infection [20,21], and surgical site infection [22,23]. PLR is a simple inflammatory marker that does not need any additional laboratory testing, and easily calculated by the platelet count/lymphocyte count formula.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were rejected for several reasons, such as irrelevant research (n = 1), duplicate research (n = 1), commentary (n = 2), or review (n = 1). Finally, 7 references were included in this study [17,18,[21][22][23][24][25]. The details of the study selection process can be found in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…However, the patient selection and reference standard were both high risk, because 6 studies did not avoid case-control designs and interpretations of reference standards were not blinded [17,18,[21][22][23]25]. In addition, the thresholds of FIB for the 7 studies were not pre-specified; therefore, all index texts were high risk [17,18,[21][22][23][24][25].…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations